Poisoning by Thiloa glaucocarpa (Combretaceae) in cattle in the semiarid regions of Paraíba and Pernambuco, Brazil - Almeida, Thais H.S.; Albuquerque, Raquel F.; Almeida, Valdir M.; Silva Filho, Givaldo B.; Chaves, Hisadora A.; Freitas, Sílvio H.; Riet-Correa, Franklin; Mendonça, Fábio S. (Brazilian Journal of Veterinary Pathology, 2017)
The aim of this study was to describe the epidemiological, clinical and pathological aspects of spontaneous poisoning by Thiloa glaucocarpa in cattle in the semiarid region of Paraíba and Pernambuco, Brazil. Eight adult cattle were examined and of those, five were necropsied. The main clinical signs consisted of dehydration, dry nose, ascites and subcutaneous edema. Renal function tests resulted in significant changes. The gross macroscopy consisted of significant fluid accumulation in the abdominal and thorax cavities, and edema of lungs, subcutaneous tissues, perirenal tissue and abomasal folds. Histologically, the main lesions consisted of epithelial coagulation necrosis of renal convoluted tubules with presence of amorphous eosinophilic material in the lumen of the tubules. The diagnosis of poisoning by T. glaucocarpa was based on epidemiological data, clinical signs, necropsy findings, histopathological evaluation, renal serum biochemistry and plant identification in the areas of cattle pastures. After the start of the rainy season in this region, T. glaucocarpa is the main toxic plant responsible for significant economic losses. Since there is no effective treatment for animals with renal failure, it is recommended that the animals must be removed from the areas where the plant grows in the period immediately after the first rain.